Analysis of Interests and Learning Outcomes of Elementary School Natural Sciences Through Contextual Approach: Analisis Minat dan Hasil Belajar Ilmu Pengetahuan Alam Sekolah Dasar Melalui Pendekatan Kontekstual - Adenan, Muhammad Baharudin; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2021)
This study discusses the analysis of interest and learning outcomes in elementary school natural sciences through a contextual approach. The existence of this, the researchers found several problems that need to be researched. The problem is about how interest in learning natural science in elementary schools through a contextual approach and how the learning outcomes of elementary school natural science through a contextual approach. This problem made the researcher take a qualitative descriptive research approach using the literature study method. Sources of data obtained come from journals, articles and other previous research. The source of the data taken in the study must be at least the last five years. The results obtained from the study showed that students experienced an increase in interest in learning and learning outcomes of natural science using a contextual approach. These results make the researchers conclude that a contextual approach can affect students' interest and learning outcomes in natural science material.